Clinical performance of vital bleaching techniques - Bernardon, Jussara K; Sartori, Neimar; Ballarin, Andressa; Perdigão, Jorge; Lopes, Guilherme Carpena; Baratieri, Luiz Narciso (Operative dentistry, 2010)
This study compared the clinical outcome of bleaching techniques in vital teeth. After IRB approval and informed consent, 90 subjects were selected based on the shade of their anterior teeth (A2 or darker, Vita Classic shade guide). Subjects were assigned to three treatment groups in a split-mouth study design: Group I: HB (at-home bleaching with 10% carbamide peroxide for two weeks) vs OBL (in-office bleaching with 35% hydrogen peroxide, two sessions, two-week intervals, with light irradiation); Group II: OB (in-office bleaching without light irradiation) vs OBL; Group III: HB vs combination (one session plus HB). Color change and color rebound (deltaE) were measured for a 16-week period. Color measurements were carried out with both a spectrophotometer and a shade guide at baseline, 1, 2, 4, 8 and 16 weeks. Tooth sensitivity was evaluated using a VAS scale for 15 days. Both the Student's t-test and Tukey-Kramer test were used to analyze the results (p < 0.05). After one week, one session of OBL followed by HB resulted in lower color values, compared with the other bleaching methods. Group III resulted in the least shade values at one-week evaluation, when compared with the other bleaching methods. After two weeks, HE alone resulted in similar color changes as OB, OBL and OBL+HB. The use of light irradiation did not improve bleaching efficacy (OB = OBL). OBL and OB resulted in higher sensitivity rates than HB.